MODELS OF ECONOMIC DEVELOPMENT OF COUNTRIES TRANSITIONING TO A MARKET ECONOMY (Intent Research Scientific Journal, 2023)
Market economy models include mixed economy, social market economy, and corporate economy typical of economically developed countries. The mixed economy model is a type of market economy that provides high labor productivity, abundance of benefits, the most advanced technology and a highly skilled labor force. This mod will have a variety of properties. Individual and accounting forms of private property will be prioritized, state and non-state property, state and non-state sectors of the economy will develop.